Characteristics and clinical outcomes of head-injured cyclists with and without helmets in urban and rural areas of Taiwan: A 15-year study. (17th February 2017) - Kuo, Chia-Ying; Chiou, Hung-Yi; Lin, Jia-Wei; Tsai, Shin-Han; Lin, Mau-Roung; Chiang, Yung-Hsiao; Lin, Chien-Min; Chu, Shu-Fen; Liou, Tsan-Hon; Chiu, Wen-Ta
ABSTRACT: Objective : Bicycle riding is increasingly popular in Taiwan, but the number of cyclists injured and cyclists' death rates are both increasing. The aim of this study was to investigate the different characteristics and clinical outcomes of traffic accident–related head injuries among cyclists in urban and rural areas. Methods : Records of 812 patients (533 urban and 279 rural) admitted to 27 hospitals in Taipei City and Hualien County as the result of a traumatic head injury while bicycling between 1998 and 2013 were retrieved for study. Demographics, details about the accident, protective helmet use, and clinical outcomes were then subjected to analysis. Results : Urban victims were more likely to be injured during morning and early evening rush hours and rural victims during the day; most urban victims were between 19 and 34 years of age and injured in the slow lane; rural victims tended to be younger or older and were injured in the fast lane (all P ≤.001). Riders who wore a helmet were less likely to suffer loss of consciousness (odds ratio [OR] = 0.31), amnesia (OR = 0.069), neurological disorders (OR = 0.205), or facial fractures (OR = 0.369). Older age, more severe head injuries, and bicycle–motor vehicle collisions influenced the severity of symptoms on admission and the residual effects at discharge. Conclusions : Differences in the characteristics of injuries in urban and rural areas and the utilization of protective helmets may help government authorities adopt appropriate policies to promote safer and more enjoyable cycling.